Programa lúdico de fútbol 7 en el desarrollo integral en estudiantes del sexto grado de primaria de la Institución Educativa inicial primaria secundaria de menores 601486 Alexander Von Humboltd, Punchana 2024 - Navarro Gutierrez, Freddy Junior (2025)
The study aimed to evaluate the effect of the recreational 7-a-side football program on the holistic development of sixth-grade primary school students at the Alexander Von Humboldt Educational Institution 601486, Punchana 2024. The analysis was conducted with a quantitative approach, evaluative type, and quasi-experimental design, implementing both a pre-test and a post-test; with a population composed of 113 students, and a convenience sample of 56 students, with 28 in the experimental group (6th "B") and 28 in the control group (6th "A"). In this regard, the results determined a higher mean of 76±16.01 standard deviation for the experimental group, compared to the control group which achieved a mean of 60.04±6.57 standard deviation. In view of the presented differences, it was concluded that the playful 7-a-side football program has a significant effect on the overall development of the students belonging to the experimental group with a p-value = 0.000 < α=0.05, accepting the research hypothesis.